Shrimp humoral responses against pathogens: antimicrobial peptides and melanization - Tassanakajon, Anchalee; Rimphanitchayakit, Vichien; Visetnan, Suwattana; Amparyup, Piti; Somboonwiwat, Kunlaya; Charoensapsri, Walaiporn; Tang, Sureerat (Developmental and comparative immunology, 2018)
Diseases have caused tremendous economic losses and become the major problem threatening the sustainable development of shrimp aquaculture. The knowledge of host defense mechanisms against invading pathogens is essential for the implementation of efficient strategies to prevent disease outbreaks. Like other invertebrates, shrimp rely on the innate immune system to defend themselves against a range of microbes by recognizing and destroying them through cellular and humoral immune responses. Detection of microbial pathogens triggers the signal transduction pathways including the NF-κB signaling, Toll and Imd pathways, resulting in the activation of genes involved in host defense responses. In this review, we update the discovery of components of the Toll and Imd pathways in shrimp and their participation in the regulation of shrimp antimicrobial peptide (AMP) synthesis. We also focus on a recent progress on the two most powerful and the best-studied shrimp humoral responses: AMPs and melanization. Shrimp AMPs are mainly cationic peptides with sequence diversity which endues them the broad range of activities against microorganisms. Melanization, regulated by the prophenoloxidase activating cascade, also plays a crucial role in killing and sequestration of invading pathogens. The progress and emerging research on mechanisms and functional characterization of components of these two indispensable humoral responses in shrimp immunity are summarized and discussed. Interestingly, the pattern recognition protein (PRP) crosstalk is evidenced between the proPO activating cascade and the AMP synthesis pathways in shrimp, which enables the innate immune system to build up efficient immune responses. •The progress research on the major humoral responses in shrimp, antimicrobial peptides and melanization, are summarized.•Toll and Imd pathways regulate gene expression of different shrimp antimicrobial peptides.•Components of the proPO system are discovered and their participation in the proPO cascade are revealed.•The immune crosstalk between the proPO activating cascade and the AMP synthesis pathways in shrimp is proposed.